Using Discrete Choice Experiment to Determine Willingness to Pay for Interferon-Beta Drugs by Multiple Sclerosis Patients: Willingness to Pay for Interferon-Beta Drugs in Multiple Sclerosis Patients - Rahimi, Farimah; Rasekh, Hamid Reza; Peiravian, Farzad; Abbasian, Ezatollah (Iranian Journal of Pharmaceutical Sciences, 2018)
This study explores the effects of Interferon-β characteristics such as country of origin, injection frequency and method, monthly cost, effectiveness, and side effects on multiple-sclerosis patients’ willingness to pay. For this purpose, MS patients with a history of using Interferon-β were studied from the three major Isfahan MS centers. Choice sets were designed with a combination of attributes and levels. The variables in this experiment included interferon-β with different levels assigned to each of its attribute. Patient preferences and willingness to pay were calculated through Discreet Choice Experiment. The statistical population consisted of 358 patients deemed eligible for the study. They responded to the questionnaire and took part in interviews. Results showed that the highest willingness-to-pay value of US 223 as determined by MS patients belonged to a change of effectiveness from moderate to high. Side-effects and ease of use ranked next among patient preferences. Country of origin recorded the lowest value of the willingness-to-pay parameter. Evaluation of MS patients’ preferences as reflected in their willingness to pay plays an important role in patient’s adherence to treatment to achieve more effective results. Due to the variety of drugs in this category, it is necessary to identify and prioritize those features that are of interest to patients and that increase their utility relative to IFN-β drugs.